Severe Legionnaires’ Disease Complicated by Rhabdomyolysis and Clinically Resistant to Moxifloxacin in a Splenectomised Patient: Too Much of a Coincidence? - Theocharis Koufakis; Ioannis Gabranis; Marianneta Chatzopoulou; Anastasios Margaritis; Maria Tsiakalou (Case Reports in Infectious Diseases)
We here report a case of Legionnaires’ disease in a splenectomised patient, complicated by rhabdomyolysis and acute renal failure and characterized by a poor clinical response to moxifloxacin. Splenectomy is not included among the factors, typically associated with higher risk or mortality in patients with Legionellosis. However, our report is consistent with previous case reports describing severe Legionella infections in asplenic subjects. The possibility that functional or anatomic asplenia may be a factor predisposing to severe clinical course or poor response to therapy in patients with Legionella infection cannot be excluded, deserving further investigation in the future. More studies are required in order to clarify the underlying pathophysiological mechanisms that connect asplenia, immunological response to Legionella, and pathogen’s resistance to antibiotics.